Affective factors that influence english oral production in the 8th level basic general education students of the Unidad Educativa Particular “Oviedo”, Ibarra canton, school year 2018-2019 - Enríquez Tarapués, Nathaly Silvana (2021)
Apply methodological strategies to minimize the effect of affective factors on the oral production of the foreign language.